2009
DOI: 10.1108/14770020910990614
|View full text |Cite
|
Sign up to set email alerts
|

Direct offsets in international trade as a remedy for asymmetric information

Abstract: Purpose -The main purpose of this paper is to investigate whether purchases of capital goods through direct offset transactions (OTs) could be a more beneficial form of trade than conventional market transactions (MTs). Design/methodology/approach -An original model of trade is offered where a company from a less-developed country plans to acquire an advanced technology embodied in capital goods from a developed country's firm. The quality of technology is unknown to the buyer. The model is used to analyse the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Taylor (2012) elaborates on this proposition in several papers and provides data on the significance of offset transactions in the face of the fact that US and EU policies tend to take a stance against offsets in international trade. Baranowska-Prokop (2009) analyzes a company from a less developed country which plans to acquire an advanced technology embodied in capital goods from a firm in a developed country, where the quality of that technology is unknown to the buyer. It was shown that in the case of substantial uncertainty about the quality of the technology that is being acquired, directoffset transactions can provide insurance against the quality uncertainty and become the preferred form of trading, used instead of market transactions.…”
Section: Offset Practices and The Legal Background -An Overview Of The Literaturementioning
confidence: 99%
“…Taylor (2012) elaborates on this proposition in several papers and provides data on the significance of offset transactions in the face of the fact that US and EU policies tend to take a stance against offsets in international trade. Baranowska-Prokop (2009) analyzes a company from a less developed country which plans to acquire an advanced technology embodied in capital goods from a firm in a developed country, where the quality of that technology is unknown to the buyer. It was shown that in the case of substantial uncertainty about the quality of the technology that is being acquired, directoffset transactions can provide insurance against the quality uncertainty and become the preferred form of trading, used instead of market transactions.…”
Section: Offset Practices and The Legal Background -An Overview Of The Literaturementioning
confidence: 99%
“…Neale and Sercu (1993) describe counterpurchase as a derivative of classical barter in which goods are always valued in monetary terms. More recently, Baranowska-Prokop (2009) characterizes counterpurchase as an agreement by the initial seller to buy a specified value of goods (often stated as a percentage of the initial sales volume) from the initial buyer over a defined period of time. Companies follow different rationales to enter a counterpurchase agreement.…”
Section: Compensation Dealsmentioning
confidence: 99%
“…As the practice became more modern, segments of the State other than the military started to employ offset policies to acquire technologies in an effort to improve the efficiency of products and services. As a result of this practice, State policies have begun to promote another phenomenon: TT [3,4].…”
Section: Introductionmentioning
confidence: 99%